A new optical waveguide for telecommunication application - Sharma, Sudhir Kumar (2001)
Conducting polymer is a physical mixture of non-conducting polymer with electrically conducting material. Polyaniline is a class of conducting polymers that exists in four different forms depending on protonation and doping of the base. Starting with aniline, polyaniline is synthesized and doped with two different metals namely iron and aluminum separately. Using these films optical waveguides are fabricated. Their characteristics viz. Refractive index, propagation loss, number of modes etc., are studied using prism coupling technique. The results are discussed.